(untitled) (Medico Legal Update, 2020)
Nicotine is highly addictive plant derived alkaloid and the most important species in human use today is Nicotiana tabacum. There are direct health effects of chronic nicotine exposure. Even in low doses, nicotine causes vasoconstriction and other cardiovascular effects related to catecholamine release and promote angiogenesis, neuroteratogenicity, and possibly some cancers¹. Periodontal disease and dental cavities and have up to 48 times the risk of oropharyngeal cancers compared with people who do not use tobacco products². Low doses exposure produces fine tremor, cutaneous vasoconstriction, increased GI motility, and increase in heart rate, respiratory rate and blood pressure³. Low dose nicotine also increases mental alertness and produces euphoria and desired psychoactive effects³. Metabolism is via the hepatic cytochrome oxidase system. The half life of nicotine in the body is 1 to 4 hours and decreases with repeated nicotine exposure4.